2006
DOI: 10.1007/11861201_60
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Heterogeneous Motorised Traffic at a Signalised Intersection

Abstract: The characteristics of heterogeneous traffic (with variation in vehicle length) are significantly different from those for homogeneous traffic. The present study describes an overview of the development and validation of a stochastic heterogeneous traffic-flow simulation model for an urban single-lane two-way road, with controlled intersection. In this paper, the interaction between vehicle types during manoeuvres at the intersection are analysed in detail. Two different motorised vehicle types are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The simulation of large traffic networks can be performed in multiple real-time. Several other researchers have devised related schemes [13,14,15,16,17,18,19].…”
Section: Summary Of Ca-based Traffic Simulation Modelsmentioning
confidence: 99%
“…The simulation of large traffic networks can be performed in multiple real-time. Several other researchers have devised related schemes [13,14,15,16,17,18,19].…”
Section: Summary Of Ca-based Traffic Simulation Modelsmentioning
confidence: 99%
“…of the deterministic rules, the BML model is regarded as a deterministic model (Fukui and Ishibashi, 1996 Jin et al (2001) Lane changing behaviour at approach and departure lanes are modelled It is found that traffic performance is affected by both traffic conditions and signal control Wu et al (2005) Vehicle interactions at a Tjunction with signal control are analysed Mixed vehicle type simulation based on BML model. Vehicle compositions will affect junction capacity Deo and Ruskin (2006) Two different vehicle types, namely cars and buses, (or similar length vehicles), are simulated Mixed vehicle type simulation; analyse the effect of vehicle type distribution Spyropoulou (2007) Discusses the feasibility of using CA models to simulate signalised junction. Relationships between randomisation inputs and simulation outputs are studied (Akçelik et al, 1999;PTV, 2006).…”
Section: Iii) Biham-middleton-levine (Bml) Model For Two-dimensional mentioning
confidence: 99%